Evaluation of South Korea's Government Policy on Migrant Worker Protection in Safeguarding Labor Rights and Welfare - Hasyim, Muhammad; Barthos, Megawati (International Journal of Social Service and Research, 2025)
Migrant workers constitute an essential component of the global labor landscape, including in South Korea, which has experienced increasing reliance on foreign labor across various industrial sectors. Their presence significantly contributes to national economic growth, particularly in occupations that are less desirable to the local workforce. However, behind these economic contributions, migrant workers often face serious challenges related to legal protection, fundamental rights, and guarantees of decent welfare. Many encounter discriminatory treatment, inhumane working conditions, and obstacles in accessing legal justice. Within this context, it is crucial to evaluate the policies formulated and implemented by the South Korean government in protecting migrant workers. This study adopts a normative juridical method, using legislative and conceptual approaches. This method enables the examination and analysis of applicable legal norms, both within South Korea’s domestic regulations and in international legal instruments such as ILO conventions and relevant human rights declarations. The analysis is conducted through the review of primary legal materials, including statutory regulations, as well as secondary sources such as literature, scholarly articles, and academic documents discussing legal protection, workers' rights, and principles of social justice. The study aims to develop a normative understanding of how the state should ensure the rights and welfare of migrant workers in a fair, equitable, and humane manner, and to provide a theoretical foundation for the development of more inclusive and responsive labor policies.